2017
DOI: 10.4269/ajtmh.16-0689
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Neurocysticercosis and Hippocampal Atrophy is Related to Age

Abstract: Abstract. Neurocysticercosis (NCC) has been associated with hippocampal atrophy, but the prevalence and pathogenic mechanisms implicated in this relationship are unknown. Using a population-based, case-control study design, residents in a rural village (Atahualpa) aged ≥ 40 years with calcified NCC were identified as cases and paired to NCCfree individuals (control subjects) matched by age, sex, and level of education. Cases and control subjects underwent magnetic resonance imaging for hippocampal rating accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 26 publications
(31 reference statements)
1
23
0
3
Order By: Relevance
“…22,29,30 As detailed elsewhere, MRIs were performed with a Philips Intera 1.5T (Philips Medical Systems, the Netherlands) at Hospital-Clínica Kennedy, and included two-dimensional multi-slice turbo spin echo T1-weighted, fluid attenuated inversion recovery (FLAIR), T2-weighted, and gradient-echo sequences in the axial plane, as well as a FLAIR sequence oriented in the sagittal plane; slice thickness was 5mm with 1mm gap between slices. 29 A total of 452 MRIs, all performed in Atahualpa residents aged ≥40 years, were reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22,29,30 As detailed elsewhere, MRIs were performed with a Philips Intera 1.5T (Philips Medical Systems, the Netherlands) at Hospital-Clínica Kennedy, and included two-dimensional multi-slice turbo spin echo T1-weighted, fluid attenuated inversion recovery (FLAIR), T2-weighted, and gradient-echo sequences in the axial plane, as well as a FLAIR sequence oriented in the sagittal plane; slice thickness was 5mm with 1mm gap between slices. 29 A total of 452 MRIs, all performed in Atahualpa residents aged ≥40 years, were reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the potential lack of resolution of CT to detect small cystic lesions in the brain parenchyma, subarachnoid space, or ventricular cavities, we used information provided by brain magnetic resonance imaging (MRI) performed in the same population for other research purposes, as part of the Atahualpa Project. 22,28,29 As detailed elsewhere, MRI was performed with a Philips Intera 1.5T (Philips Medical Systems, The Netherlands) at Kennedy Hospital-Clinic, and included two-dimensional multislice turbo spin echo T 1 -weighted, fluid attenuated inversion recovery (FLAIR), T 2 -weighted, and gradient-echo sequences in the axial plane, as well as a FLAIR sequence oriented in the sagittal plane; slice thickness was 5 mm with a 1-mm gap between slices. 28 A total of 452 MRIs, all performed in Atahualpa residents aged ≥40 years, were reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Given the major role of the hippocampus in memory and other cognitive functions, it is plausible to hypothesize that hippocampal atrophy could be the link to explain cognitive impairment in NCC patients. In addition, previous studies from our group have shown a significant association between NCC-related hippocampal atrophy and increasing age, 12 which, in turn, is also associated with worse cognitive performance. None of the aforementioned studies investigated the role of hippocampal atrophy or age to explain the cognitive performance of NCC patients compared with controls.…”
mentioning
confidence: 64%
“…[16] In the same population, it was demonstrated that this association is strongly related to age, suggesting that NCC-related hippocampal atrophy takes a long time to develop. [17] Interestingly, many of the studied individuals do not had epilepsy or electroencephalography evidence of paroxysmal abnormalities, showing that the association between NCC and hippocampal atrophy may occur irrespective of seizure activity (unpublished data).…”
Section: Neuroimmunology and Neuroinflammationmentioning
confidence: 88%